Experimental Studies to Verify the Effect of Chip Shrinkage Coefficient on Cutting Forces and Surface Roughness in High Speed Milling of A6061 Aluminum Alloy - Pham, Thi Hoa; Mac, Thi Bich; Banh, Tien Long; Nguyen, Duc Toan (Old Journal, 2017)
This paper studied the relationship between the cutting force, surface roughness and chip shrinkage coefficient through the affect of cutting parameters, i.e., cutting speed, feed rate and uncut chip thickness. Experimental results of the chip shrinkage coefficient, cutting force and surface roughness at various cutting parameter values for high-speed milling of A6061 aluminum alloy were presented in this study. The results show that the cutting force and surface roughness can be derived based on the relationships with chip shrinkage coefficient.